2021
DOI: 10.1186/s13071-021-04910-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of sarolaner in the clinical management of furuncular myiasis in dogs naturally infested with Dermatobia hominis (Diptera: Cuterebridae)

Abstract: Background The human botfly, Dermatobia hominis, is a common cause of furuncular myiasis in dogs in Latin America. Lesions can be single or multiple, each harboring an individual larva, presented as an erythematous nodule that causes pruritus and pain. Typical treatment consists of sedation for removal of larvae by surgical incision or manual pressure. Medications to kill the larva before its extraction can reduce inflammation and discomfort and provide a less traumatic larval removal. Isoxazol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
6
1
Order By: Relevance
“…The larvae were removed after 6 h to ensure that they were dead or with little motility, avoiding data misinterpretation. The ease of removal was also noted, which was noticed even in live larvae, in addition to less discomfort to the animals, as observed in another study [10]. Hence, this study believes that if the assessment was carried out within 24 h, a methodology similar to the other studies [10], e cacy would be similar.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The larvae were removed after 6 h to ensure that they were dead or with little motility, avoiding data misinterpretation. The ease of removal was also noted, which was noticed even in live larvae, in addition to less discomfort to the animals, as observed in another study [10]. Hence, this study believes that if the assessment was carried out within 24 h, a methodology similar to the other studies [10], e cacy would be similar.…”
Section: Discussionsupporting
confidence: 76%
“…Recently, publications guided companion animals' mechanical control, which causes intense discomfort, sometimes requiring sedation in heavily infested animals [6-9], although several curative and preventive protocols are available for large animal treatment. It is possible to mention chemical products and medications that act in larvae and larval control elimination, such as macrocyclic lactones [8], benzolueiras [9], organophosphates [5], and isoxazolines [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared with a study that also used lotilaner in cats against C. bezziana and two other reports, one that used sarolaner in dogs and another topic uralaner in cats, we had lower e cacy. This is probably due to the methodology used since it was veri ed after only 6 h, which is different from the other three reports that were evaluated in a period ranging from 24 to 48 h after drug administration [16,10,11].…”
Section: Discussionmentioning
confidence: 80%
“…However, more recent studies have considered pharmacological treatment with the use of antiparasitic formulations also to be effective. The use of fluralaner for the expulsion of larvae in domestic cats ( Campos et al, 2021 ) and the use of sarolaner on dogs have been reported ( Andriotti et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%